1994
DOI: 10.1128/aac.38.8.1794
|View full text |Cite
|
Sign up to set email alerts
|

In vitro anti-Mycobacterium avium activities of quinolones: predicted active structures and mechanistic considerations

Abstract: The relationship between the structures of quinolones and their anti-Mycobacterium avium activities has been previously derived by using the Multiple Computer-Automated Structure Evaluation program. A number of substructural constraints required to overcome the resistance of most of the strains have been identified. Nineteen new quinolones which qualify under these substructural requirements were identified by the program and subsequently tested. The results show that the substructural attributes identified by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 41 publications
(45 reference statements)
0
14
0
Order By: Relevance
“…Analysis of the quinolone structureactivity relationship showed that these seven compounds shared certain structural features (C-8 with or lacking a substitution, N-1 cyclopropyl group, a ring at C-7, and a fluorine at C-6) (see Table 1). Quinolone structure-activity relationship analyses done to date for quinolones and mycobacteria (21,24,32,38) were not based on target inhibition, as in our study, but on MICs, which are the result of target inhibition and many other factors of activity, such as cell wall permeability and efflux (19). Moreover, these analyses were done with nontuberculous mycobacteria (M. smegmatis, M. avium, and M. fortuitum) and not with M. tuberculosis.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the quinolone structureactivity relationship showed that these seven compounds shared certain structural features (C-8 with or lacking a substitution, N-1 cyclopropyl group, a ring at C-7, and a fluorine at C-6) (see Table 1). Quinolone structure-activity relationship analyses done to date for quinolones and mycobacteria (21,24,32,38) were not based on target inhibition, as in our study, but on MICs, which are the result of target inhibition and many other factors of activity, such as cell wall permeability and efflux (19). Moreover, these analyses were done with nontuberculous mycobacteria (M. smegmatis, M. avium, and M. fortuitum) and not with M. tuberculosis.…”
Section: Discussionmentioning
confidence: 99%
“…A database of 158 quinolones with known anti-M. avium-M. intracellulare complex activities has been built up from several articles by Klopman et al (20,21,23). Each quinolone was characterized by a set of 145 TIs specific to each molecule.…”
Section: Methodsmentioning
confidence: 99%
“…On the basis of the data of Klopman et al (20,21,23), the quinolones studied here were separated into active and inactive compounds according to their MICs around a cutoff of 32 g/ml. In accordance with the studies of Klopman et al, this cutoff was selected since it allowed a clear differentiation between active and inactive drugs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wells were periodically observed under a microscope to check for cell viability or Fig. 1; synthesis and other characteristics of these compounds are described elsewhere (11,12).…”
mentioning
confidence: 99%